Estrategias de medio ambiente de la cooperación internacional - Pereira Jerez, David; Rodríguez Ariza, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
This article is the result of an analysis of Environmental Strategies published by the most important International Co-operation Agencies. They try to integrate the environmental elements as well as the concept of sustainable development, to turn them into a first level strategic priority fully assumed in their Co-operation Strategies. Some of their basic characteristics are compiled and synthesised, to analyse aspects such as principles and objectives, scope, how they relate with other strategies such as Poverty Reduction and Gender, and to see the measures proposed.